About „filomacka“ tradition during the inter-war period in Vilnius: “Wiwlasy” by Edward Walewski (1926) and a newspaper „Filomatka“ (1929). - Fedorowicz, Irena (Vilnius University Open Series, 2021)
In Vilnius that was considered as spiritual capital of Grand Duchy of Lithuania in the period of inter-war, and mainly in ’20s of the XX century still was very living romanticism tradition. The important person and symbolic messenger of this tradition was Adam Mickiewicz, the most famous polish-lithuanian poet, polish national prophet. Very noticeable was the fact that the best known literary scientists, like: J. Kallenbach, S. Pigoń, K. Górski were employed in Polish Literature Department, in Faculty of Humanities of Stefan Batory University. Wladysław Mickiewicz – son of the poet Adam Mickiewicz, also his biographer visited Vilnius and university in 1922. In 1926 was published collection of poems named Wiwlasy. Jamb na stulecie filomatów by Edward Walewski. It consists of 48 sonnets that describe the activity of „Filomaci and Filareci“ Society members. The lyrics refer also to people (J. Lelewel, K. Kontry, E. Groddeck), and places (Nowogródek, Tuhanowicz, Bolcienik) related to some meaningful locations connected with „Filomaci“ trial case. The other significant literary event was the attempt to issue due to efforts of some teachers K. Adamska-Roubina, S. Szemitówna-Cywińska and O. Zambrzycka-Swianiewiczowa, in Vilnius in 1929, the school newspaper „Filomatka“. Till our times only one archival copy is left, there is no evidence if there were more copies. It is necessary to mention that both literary events, despite their weak response, are interesting and worth mentioning examples of still alive tradition of „Filomaci“ in Vilnius.
Keywords: inter-war period; Vilnius; „Filomaci“ tradition